REPRESENTASI NILAI SOSIAL DALAM CERPEN ZAMRUD KARYA DANARTO: KAJIAN SOSIOLOGI SASTRA - Dinda Amalia; Desti Fatin Fauziyyah; Meity Suratiningsih (Jurnal Bastra (Bahasa dan Sastra), 2026)
This study aims to explore and identify the social values contained in Danarto's short story Zamrud using a sociological study of literature by analyzing it and describing the influence between literature and society. This research is a descriptive qualitative study. Data collection techniques in this study include reading, note-taking, documentation, and literature studies. While the data analysis technique that will be carried out is using the Miles and Huberman model regarding social values. The data sources in this analysis are Danarto's short story Zamrud and several supporting books for the research. Zamrud is a short story found in Danarto's short story collection Ikan-Ikan dari Laut Merah. The results of the short story analysis show 9 social values consisting of 6 values of compassion, 2 values of responsibility, and 1 value of harmony in life. This research is expected to increase knowledge for researchers in the field of literature and provide an understanding for readers of literary works regarding social values.